Using high resolution peripheral quantitative computed tomography to evaluate bone health and relative energy deficiency in sport risk in elite winter sport athletes - Smith, E. M. (University of Calgary, 2024)
Relative Energy Deficiency in Sport (REDs) is a syndrome resulting from problematic low energy availability (LEA). Low areal bone mineral density (aBMD) is a primary indicator of LEA and is measured at the hip or spine by dual X-ray absorptiometry (DXA). High-resolution peripheral quantitative computed tomography (HR-pQCT) measures volumetric BMD (vBMD), microarchitecture, geometry, and estimated strength reported as failure load. The objective of this study was to assess the differences in bone parameters using HR-pQCT in elite winter sport athletes identified as at-risk or not at-risk of REDs using the Clinical Assessment Tool (CAT2). Participants included 101 athletes (24.1?4.4 SD years; 53% female). HR-pQCT scans of the non-dominant radius and left tibia were analyzed and compared to DXA results. Seventeen athletes (17%; 71% female) were at-risk of REDs based on the CAT2. Bland-Altman plots suggested that compared to aBMD, Z-scores were more like failure load (ICC=0.42±0.10) than vBMD (ICC=0.25±0.07). After covarying for lean mass, odds ratios (OR) suggested increased likelihood of REDs risk classification for those with low cortical thickness (radius: OR=2.14, p=0.021; tibia: OR=1.89, p=0.037), and area (radius: OR=3.04, p=0.007; tibia: OR=2.74, p=0.006), total vBMD (tibia: OR=2.06, p=0.030), and failure load (tibia: OR=2.17, p=0.033). ROC-AUC analysis showed very poor to poor (0.50<AUC<0.69) discriminatory abilities at both the radius and tibia in identifying REDs risk based on the current threshold of Z-score <-1.0 standard deviations (SD). Bone parameters were lower in athletes at-risk of REDs and results agree with the new consensus statement that HR-pQCT may identify impaired bone health in athletes at-risk of REDs. These findings are novel in approaching REDs using HR-pQCT and in the population of elite winter sport athletes. Future directions should explore longitudinal studies utilizing bone change over time as this may provide greater insight into REDs risk.